Muslim ummah, international organisations, and human development in the MMCs - Hossain, Ishtiaq (Springer, 2012)
This chapter, by examining the features and achievements of the Arab League, OIC and GCC, will endeavour to find answer to the above questions. Before getting to the main analysis, the chapter presents a brief discussion on international society from the perspective of Islam. Then the chapter in sequence,analyses the roles of the Arab League, the Otganizalion of the Islamic Conference, and the Gulf Cooperation Council in promoting peace and development in the pur-suit of human development inthe 47 Muslim majority countries (MMCs; the focus of this Book), all of which are members of one or all three of these international organisations.